"Labels Don't Define Schools!": Developing Justice-Oriented Teaching Dispositions through Service-Learning Opportunities - Coffey, Heather; Webster, Nicole; Heafner, Tina L. (International Journal of Research on Service-Learning in Teacher Education, 2016)
This project presents findings from a study that combined service-learning with a university course on Democracy and Education, which is part of the liberal studies curriculum. The authors present a rationale for offering a service-learning partnership with a high-poverty, urban middle school in order to facilitate the development of justice-oriented teaching dispositions in first year university students who demonstrated a predilection for education-related academic majors (i.e. teaching, counseling, administration). Drawing on extant literature in the fields of justice-oriented teacher education and service-learning, the authors propose this model has potential for preparing preservice teachers for working in urban school settings. Through analysis of surveys and weekly reflections, the authors discuss how a liberal studies course with an embedded service-learning component with an emphasis on major issues in urban public school education has the potential to transform how first year university students think about schooling. Key findings indicate that upon completion of course readings, assignments, and service experience in a large urban middle school, many students began to develop justice-oriented dispositions, which is promising for an increasingly diverse socio-economic, ethnic, and language minority student population in the United States.